2012
DOI: 10.1177/0956797612450031
|View full text |Cite
|
Sign up to set email alerts
|

The Emotionally Intelligent Decision Maker

Abstract: In two experiments, we examined how a core dimension of emotional intelligence, emotion-understanding ability, facilitates decision making. Individuals with higher levels of emotion-understanding ability can correctly identify which events caused their emotions and, in particular, whether their emotions stem from events that are unrelated to current decisions. We predicted that incidental feelings of anxiety, which are unrelated to current decisions, would reduce risk taking more strongly among individuals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(30 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Additionally, future work can enrich our understanding via an examination of individual-difference variables that may play a role. For example, emotional intelligence (Mayer & Salovey, 1997;Yip & Côté, 2013) might moderate the effect of incidental This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Additionally, future work can enrich our understanding via an examination of individual-difference variables that may play a role. For example, emotional intelligence (Mayer & Salovey, 1997;Yip & Côté, 2013) might moderate the effect of incidental This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…On this view, anxiety increases the motivation to reduce uncertainty, and people often do so by selecting more certain options. Supporting this idea, studies have found that, when faced with two options that differ in terms of their risk and reward (e.g., a job with high pay but low job security vs. one with average pay but high job security), people experiencing anxiety tend to prefer the uncertainty-reducing, safer option (Raghunathan & Pham, 1999;Yip & Côté, 2013). Extending this logic to the domain of perspective taking, we suggest that people are usually more certain about their own cognitions than the cognitions of others.…”
Section: Mental-state Reasoningmentioning
confidence: 99%
“…In this way, it is important to say that the acquisition of knowledge is mediated by emotions (Khosla et al, 2009; Miller, 2010; Yip and Côté, 2013). If a positive climate is offered in the university environment for the mastery of optimized emotional management, the experiences of multiple teachings are strengthened and reach completeness in their internalization and implementation by individuals (Woods, 2010, 2012; Erkutlu and Chafra, 2014; Goggin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%